2017
DOI: 10.4236/ajps.2017.88133
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Yield and Stability Analysis of Wheat under Different Crop Management Systems across Agro-Ecosystems in India

Abstract: The objectives of the study were as follows: 1) to evaluate the GxExM for wheat genotypes; 2) to predict yield performance and identify high stable wheat genotypes in different management practices; and 3) to make genotype-specific management and high performing genotype recommendations within and across agro-ecological regions. A diverse set of twenty-one genotypes was evaluated over three years (2012, 2013 and 2014) under two levels of crop management practices (CT and ZT) across three agro-ecological regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 53 publications
(36 reference statements)
0
9
0
Order By: Relevance
“…Thus, there is a particular need to gain heat tolerance and develop heat-tolerant new germplasm through wheat breeding (Bhatta et al, 2008). The genotype selection depends on the understanding of the interaction among the genotypes, environment, and crop management practices which can be characterized using statistical methods (Jat et al, 2017). The variety with the highest average yield in all the test environment alone cannot be used for recommendation to the farmers; analysis of the stability of variety in the environment that is G Â E interaction and physiological basis are also to be studied (Vergas et al, 2001;Thamson and Philips, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there is a particular need to gain heat tolerance and develop heat-tolerant new germplasm through wheat breeding (Bhatta et al, 2008). The genotype selection depends on the understanding of the interaction among the genotypes, environment, and crop management practices which can be characterized using statistical methods (Jat et al, 2017). The variety with the highest average yield in all the test environment alone cannot be used for recommendation to the farmers; analysis of the stability of variety in the environment that is G Â E interaction and physiological basis are also to be studied (Vergas et al, 2001;Thamson and Philips, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…GGE bi-plot analysis showed that genotype (G7) performed best in almost all environments except in E3 and E11 (Figure 1). If no environment is present in a sector, then vertex genotype of that sector is considered to be a poor performer in all test environments [15].…”
Section: Which-won-where Pattern Of Genotypes and Environmentsmentioning
confidence: 99%
“…According to [15]report, responsive genotypes were those having either best or the poorest performance in one or all environments. Accordingly, among the vertex genotypes G5 and G7 were identified as the high yielding genotypes while G12 and G16 were the low yielding genotypes across the testing environments ( Fig.…”
Section: Which-won-where Pattern Of Genotypes and Environmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The genotype selection is dependent on the understanding of interaction among the genotypes, environment and crop management practices which can be characterized using statistical method [29]. The variety with highest average yield in all the test environment alone cannot be used for recommendation to the farmers; analysis of stability of variety in the environment that is G × E interaction and physiological basis are also to be studied [30].…”
Section: Introductionmentioning
confidence: 99%